THE INTERPRETERS OF POSTCOLONIAL NIGERIA: WOLE SOYINKA’S VISION OF IDENTITY, CULTURE, AND SOCIO-POLITICAL CRITIQUE - Patteti, Raja Sekhar; Sampath, Gummadi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Wole Soyinka’s The Interpreters (1965) is a seminal exploration of postcolonial identity, societal contradictions, and intellectual alienation in a newly independent Nigeria. Recognized for its innovative modernist techniques, the novel foregrounds a group of educated Nigerian protagonists grappling with the ethical, cultural, and existential challenges of their era. This paper investigates the characters’ navigation of conflicting legacies—colonial modernity and indigenous heritage-while critiquing the socio-political fabric of post-independence Nigeria. Through Egbo, Sagoe, Sekoni, Bandele, and Kola, Soyinka interrogates themes of existentialism, corruption, cultural erosion, and the role of the intellectual in nation-building. This analysis highlights how The Interpreters not only articulates the disorientation of its characters but also engages with broader philosophical questions about agency, freedom, and collective identity.